Euro-Mediterranean fauna of Campodeinae (Campodeidae, Diplura) - Sendra, Alberto; Reboleira, Ana Sofia P.S. (European Journal of Taxonomy, 2020)
Campodeinae is the most diverse subfamily of Campodeidae diplurans and inhabits soils and subsurface ecosystems. These are distributed in the Palearctic area, clearly rarifying towards northern latitudes. The major taxonomic characters are chaetotaxy, shape and complexity of pretarsal structures, and secondary sexual characters. This monograph provides a taxonomic revision of the subfamily Campodeinae in the Euro-Mediterrnean region, based on extensive literature review and new material studied. It comprises detailed morphological descriptions and illustrations together with habitat and distribution data of 161 species and 14 subspecies from 10 genera: Campodea Westwood, 1842, Edriocampa Silvestri, 1933, Eutrichocampa Silvestri, 1902, Helladocampa Condé, 1984, Libanocampa Condé, 1955, Litocampa Silvestri, 1933, Oreocampa Condé, 1950, Podocampa Silvestri, 1932, Remycampa Condé 1952, and Spaniocampa Silvestri, 1933. With 116 species Campodea is the most diverse and widely distributed genus in the studied area.